The Code Mixing Between Waiters and Customers At Pizza Hut Gunung Sahari - Pangestu, Maulani; Buansari, Istihayyu (LPPM Universitas Bina Sarana Informatika, 2025)
Code mixing is part of linguistics. Many people uses code mixing in everyday conversation for example, often found when in a mall, supermarket or restaurant. Code mixing is the use of one language unit into another language. The code mixing occurs when the speaker enters a foreign language into the language that is more dominantly used. This research investigates the use of code mixing applied by waiters and customers at Pizza Hut Gunung Sahari by using descriptive qualitative method. As a result of the analysis, it can be found that there are two types of code mixing used in conversations between waiters and customers at Pizza Hut Gunung Sahari, they are Word Insertion and Phrase Insertion. The writer also found there are six reasons of code mixing used: Bilingualism, Speaker and Partner Speaking, Social Community, Situation, Vocabulary and Prestige. Based on Khairunas theory using code mixing can increase knowledge in other languages and if overeating is used it will have a bad effect because the speaker will always rely on code mixing and can change the speaker's accent.